The Influence of Foreign Ownership, Political Connection, Managerial Ownership, and Dividend Policy on The Financial Performance of Retailing Sub-Sector Companies Listed on The IDX - Yohana Kezia Koeswandono; Revi Arfamaini (Journal Research of Social Science, Economics, and Management, 2026)
Company financial performance describes a company’s current financial condition and provides an estimate of its future prospects, which are influenced by management and operational activities, as well as the company’s approach to managing and utilizing its resources. This study aims to analyze the influence of foreign ownership, political connections, managerial ownership, and dividend policy on the financial performance of consumer cyclicals companies in the retailing sub-sector listed on the Indonesia Stock Exchange (IDX) during the period 2019–2024. This study uses secondary data from 19 consumer cyclicals companies in the retailing sub-sector listed on the Indonesia Stock Exchange or obtained directly from the companies’ websites, covering six consecutive years (2019–2024). The data are selected based on purposive sampling criteria, resulting in a total of 114 observations. A quantitative approach is employed, including Classical Assumption Testing, outlier removal, and the Cochrane–Orcutt method. Additionally, statistical tests such as Multiple Regression Analysis, the t-test, and the Coefficient of Determination (R²) are used to analyze the data. The results of this study, analyzed using SPSS, show that managerial ownership influences a company’s financial performance. However, foreign ownership, political connections, and dividend policy do not significantly affect financial performance. This study highlights the significant impact of managerial ownership on financial performance, while foreign ownership, political connections, and dividend policy do not appear to have a substantial effect.